THE EFFECTIVENESS OF THE GRAMEEN BANK SYSTEM IN OVERCOMING NON-PERFORMING LOANS IN MITRA DHUAFA COOPERATION JAKARTA - Maya Aditya Vusvita (Scientia Integritas Utama, 2023)
KOMIDA as a microfinance institution has carried out a non-performing credit control strategy through the grameen bank system. This study aims to analyze the influence of human capital (X1), social capital (X2) and SOP (X3) on the effectiveness of the grameen bank system in controlling problem loans at the Komida Central Office. This research was conducted at the Mitra Dhuafa Cooperative Headquarters Jakarta for 2 months, April – May 2012. The research design used was descriptive and associative. The population in this study were 36 employees of the Jakarta Mitra Dhuafa Cooperative Head Office. Due to the relatively small number of populations that can be reached by researchers as a whole, a saturated sample is used. Data were analyzed by multiple linear regression. The results of the research show that (1) human capital,